2009
DOI: 10.1038/ng.500
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analyses of genome-wide association studies identify multiple loci associated with pulmonary function

Abstract: Pulmonary function is an easily measurable and reliable index of the physiological state of the lungs and airways 1 . Pulmonary function also predicts mortality in the general population, even among people who have never smoked (never-smokers) who have only modestly reduced pulmonary function and no respiratory symptoms 2,3 . The peak level of pulmonary function attained in early adulthood and its subsequent decline with age are likely influenced by genetic and environmental factors. Tobacco smoking is a major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

33
597
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 556 publications
(639 citation statements)
references
References 76 publications
33
597
6
Order By: Relevance
“…Importantly, the Charge consortium again using a large discovery population of 20,890 subjects also showed genome wide association with FEV1 at the INTS12/GSTCD/NPNT locus as well as describing additional signals (Hancock et al, 2010). This region encompasses genes Intergrator Complex Subunit 12 (INTS12), GSTCD and nephronectin (NPNT).…”
Section: Forced Expiratory Volume In 1 Secondmentioning
confidence: 94%
See 4 more Smart Citations
“…Importantly, the Charge consortium again using a large discovery population of 20,890 subjects also showed genome wide association with FEV1 at the INTS12/GSTCD/NPNT locus as well as describing additional signals (Hancock et al, 2010). This region encompasses genes Intergrator Complex Subunit 12 (INTS12), GSTCD and nephronectin (NPNT).…”
Section: Forced Expiratory Volume In 1 Secondmentioning
confidence: 94%
“…Hancock and colleagues study found the most significant association to involve SNP rs17331332 located near NPNT (P = 4.00 x 10 -10 ) ( Table 1) (Hancock et al, 2010;Repapi et al, 2010). To date, seven meta-analyses of GWAS have now been completed and identified SNP associations with FEV1 and/or FEV1 decline (Hancock et al, 2012;Hancock et al, 2010;Repapi et al, 2010;Soler ArtigasLoth, et al, 2011;Tang et al, 2014;Wain L, 2015).…”
Section: Forced Expiratory Volume In 1 Secondmentioning
confidence: 94%
See 3 more Smart Citations